Leaf Starch Turnover Occurs in Long Days and in Falling Light at the End of the Day . Issue 4 (29th June 2017) - Fernandez, Olivier; Ishihara, Hirofumi; George, Gavin M.; Mengin, Virginie; Flis, Anna; Sumner, Dean; Arrivault, Stéphanie; Feil, Regina; Lunn, John E.; Zeeman, Samuel C.; Smith, Alison M.; Stitt, Mark
Abstract : Starch in Arabidopsis leaves is increasingly liable to degradation with time after dawn, so that accumulation slows and turnover in response to falling light accelerates as the day proceeds. Abstract: We investigated whether starch degradation occurs at the same time as starch synthesis in Arabidopsis ( Arabidopsis thaliana ) leaves in the light. Starch accumulated in a linear fashion for about 12 h after dawn, then accumulation slowed and content plateaued. Following decreases in light intensity, the rate of accumulation of starch declined in proportion to the decline in photosynthesis if the decrease occurred <10 h after dawn, but accumulation ceased or loss of starch occurred if the same decrease in light intensity was imposed more than 10 h after dawn. These changes in starch accumulation patterns after prolonged periods in the light occurred at both high and low starch contents and were not related to time-dependent changes in either the rate of photosynthesis or the partitioning of assimilate between starch and Suc, as assessed from metabolite measurements and 14 CO2 pulse experiments. Instead, measurements of incorporation of 13 C from 13 CO2 into starch and of levels of the starch degradation product maltose showed that substantial starch degradation occurred simultaneously with synthesis at time points >14 h after dawn and in response to decreases in light intensity that occurred >10 h after dawn. Starch measurements in circadian clock mutants suggested that the clock influences the timing of onset of degradation. We conclude that the propensity for leaf starch to be degraded increases with time after dawn. The importance of this phenomenon for efficient use of carbon for growth in long days and for prevention of starvation during twilight is discussed.